Особливості сучасних збройних конфліктів в умовах глобалізації - Луцишин, Галина (Видавництво Львівської політехніки, 2014)
Розглянуто особливості сучасних збройних конфліктів, причини їх виникнення і розвитку у контексті глобальних політичних процесів. Показано, що більшість збройних конфліктів є відчутними для України, зокрема, через участь у міжнародних миротворчих операціях, міграцію населення з районів конфлікту через Україну, евакуацію українських громадян із зон конфлікту. Contemporary armed conflicts pose a significant threat to humanity as they may expand in the context of globalization, development of environmental disasters, negative humanitarian consequences associated with growing numbers of refugees. The article deals with special features of contemporary armed conflicts, identification of reasons for the emergence and evolution of armed conflict in the context of global political processes. This study is of immediate interest as, among other things, most armed conflicts have some bearing on Ukraine as well, for example, due to more active migration of people from areas of conflict through Ukraine and problems related to the evacuation of Ukrainian citizens from the area of conflict. In addition, Ukraine is involved in international peace-keeping operations. So, the study of special features of contemporary armed conflicts, the role and position of international organizations and some states is an important issue. The article applies general scientific methods such as systemic, comparative, and structural functional methods. They allow a comprehensive analysis of the evolution of contemporary armed conflicts and the development of practical approaches to conflict resolution. The article is empirically based on UN research, monitoring results of the Stockholm International Peace Research Institute, media materials which are used to analyze the contemporary state and prospects of the evolution of contemporary armed conflicts. Through the analysis of contemporary armed conflicts, the author identifies their main characteristics – a more pronounced international nature of armed conflicts; engagement ofcivilians in warfare; frequent application of asymmetric action between conflicting parties which makes conflicts difficult to predict and uncontrollable; transformation of conflict management methods which produces different transitions from conflict escalation to deescalation. The problem of armed conflict is highly relevant and holds a prominent place in the system of contemporary international relations.
Special features of contemporary armed сonflicts in the context of globalization
Keywords: збройні конфлікти; глобалізація; міжнародні організації; миротворча діяльність; тероризм; асиметричні конфлікти; врегулювання конфліктів; armed conflicts; globalization; international organizations; peace-keeping activities; terrorism; asymmetric conflicts; conflict resolution methods